Increasing stroke patients' success in self-medication programs using an interdisciplinary cognitive rehabilitation approach. - Purdy, Mary (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2007)
Rehabilitation programs strive to help patients become more independent in all aspects of daily living. Therefore, management of a patient's healthcare requirements should be an integral part of the rehabilitation program, including management of medications. Some rehabilitation programs implement self-medication programs (SMP); however, patients with cognitive deficits are often excluded. This study explored whether patients with cognitive deficits due to stroke could successfully complete an SMP using an interdisciplinary cognitive rehabilitation approach. Twenty-seven stroke patients and 36 debilitated patients with cognitive deficits participated in an SMP. A nurse and a pharmacist educated patients on their medications, and a speech-language pathologist provided cognitive rehabilitation to the stroke patients, which incorporated information from the SMP. Eighty-one percent of the stroke patients successfully completed the SMP, compared to 36% of the debilitated patients. Thus, an interdisciplinary approach to medication management for cognitively impaired stroke patients holds promise.
3 citations (Crossref) [2023-10-31] Place: United States Purdy, Mary. Southern Connecticut State University, Department of Communication Disorders, USA. purdym1@southernct.edu
Keywords: *Cognition Disorders/rh [Rehabilitation]; *Patient Care Team/og [Organization & Administration]; *Patient Education as Topic/og [Organization & Administration]; *Self Administration; *Stroke/co [Complications]; Aged; Analysis of Variance; Case-Control Studies; Cerebrovascular Accident; Cognition Disorders; Cognition Disorders/et [Etiology]; Cognition Disorders/px [Psychology]; Curriculum; Humans; Length of Stay; Length of Stay/sn [Statistics & Numerical Data]; MLCS; MLOWN; Middle Aged; Needs Assessment; Nursing Assessment; Nursing Evaluation Research; Patient Care Team; Patient Education; Pharmacy Service; Hospital; Pharmacy Service; Hospital/og [Organization & Administration]; Problem Solving; Program Evaluation; Rehabilitation Nursing; Rehabilitation Nursing/og [Organization & Administration]; Self Administration; Self Administration/mt [Methods]; Self Administration/px [Psychology]; Severity of Illness Index; Speech-Language Pathology; Speech-Language Pathology/og [Organization & Administration]; Treatment Outcome; aged; analysis of variance; article; case control study; cerebrovascular accident; cognitive defect; curriculum; dept.cmd; drug self administration; evaluation; health care quality; hospital pharmacy; hospitalization; human; length of stay; methodology; middle aged; needs assessment; nursing assessment; nursing evaluation research; organization and management; patient care; patient education; problem solving; psychological aspect; rehabilitation nursing; speech disorder; statistics; treatment outcome